Curcumin encapsulated in the complex of lysozyme/carboxymethylcellulose and implications for the antioxidant activity of curcumin. (September 2015) - Li, Zhenshun; Wang, Yuntao; Pei, Yaqiong; Xiong, Wenfei; Zhang, Chunlan; Xu, Wei; Liu, Shilin; Li, Bin
Abstract: A facile approach was investigated to encapsulate and protect curcumin (Cur) by self-assembly of lysozyme (Ly) and carboxymethylcellulose (CMC) of different degrees of substitution (DSs). This work studied the influence of Ly–CMC coacervates on the binding, solubility and stability of Cur. The interactions of Cur with Ly–CMC coacervates were researched by UV–vis, steady-state fluorescence, synchronous fluorescence and circular dichroism spectra. These results were explained in terms of the formation of Ly–CMC coacervates with electrostatic interaction, which led to unfold the structure of Ly for providing Cur with more hydrophobic microenvironment than free Ly. Meanwhile, the CMC of higher DS provide more negative charges, and produce more attraction to Ly than that of lower DS values. Moreover, the coacervates of Ly–CMC of higher DS are found to be superior for enhancing the stability of Cur. Our work provided a new insight for understanding the biomolecule protective system based on protein/polysaccharide complexes. Highlight: Lysozyme and carboxymethylcellulose coacervates were formed with electrostatic interaction. The coacervates could encapsulate and protect curcumin by unfolding the structure of lysozyme for providing curcumin with more hydrophobic microenvironment than by lysozyme alone. Carboxymethylcellulose of higher DSs is found to have larger affinity to lysozyme, which is more suitable for curcumin protection.